Ambient Temporalities: Rethinking Object-Oriented Time through Kant, Husserl, and Heidegger - Stephenson Jamie (Open Philosophy)
Immanuel Kant is often conveyed as a Platonic or Newtonian thinker of the temporal, expressing time as an absolute and continuous repository wherein all objects occur. However, employing themes from his aesthetic writings, what happens when Kantian “sublime” time is reoriented towards a more discontinuous temporal register? This essay employs just such a reading, while also utilising Graham Harman’s Object-Oriented Ontology (OOO), as a methodological device for rethinking both Kantian and object time as neither solely continuous nor discontinuous, but somewhere inbetween these two determinations, in what I term their “ontological ambience.” By doing so I offer a critique of both Kantian orthodoxy and Harmanian OOO, via a comparative analysis of (1) how Edmund Husserl and Martin Heidegger thematise Kantian temporality, and (2) how Harman develops their subsequent ideas about time. This schema provides post-Kantian philosophy with a provisional model for thinking posthuman time in new and productive ways: as ambient temporalities.